On New Modifications Governed by Quantum Hahn’s Integral Operator Pertaining to Fractional Calculus - Saima Rashid; Aasma Khalid; Gauhar Rahman; Kottakkaran Sooppy Nisar; Yu-Ming Chu (Journal of Function Spaces)
In the article, we present several generalizations for the generalized Čebyšev type inequality in the frame of quantum fractional Hahn’s integral operator by using the quantum shift operator  σΨqς=qς+1−qσς∈l1,l2,σ=l1+ω/1−q,0<q<1,ω≥0. As applications, we provide some associated variants to illustrate the efficiency of quantum Hahn’s integral operator and compare our obtained results and proposed technique with the previously known results and existing technique. Our ideas and approaches may lead to new directions in fractional quantum calculus theory.